2016
DOI: 10.1007/s00428-015-1901-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor regression in lymph nodes after neoadjuvant therapy for rectal carcinoma

Abstract: Neoadjuvant therapy (NAT) is mainly indicated for locally advanced rectal carcinoma. Many reports have shown that regression of the primary tumor is a prognostic factor. However, few reports to date have analyzed the potential prognostic significance of lymph node regression in rectal carcinoma. The aim of the present study is to describe the pattern of tumor regression in lymph nodes after NAT for rectal carcinoma and its potential prognostic significance. We have retrospectively reviewed 106 cases of rectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
8
0
2
Order By: Relevance
“…Moreover, in line with our observations, intra-observer agreement for the histopathological determination of regressive changes was very good [15]. Other entities in which the prognostic relevance of regression in LN metastases had a prognostic impact were breast [27] and rectal cancer [28].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, in line with our observations, intra-observer agreement for the histopathological determination of regressive changes was very good [15]. Other entities in which the prognostic relevance of regression in LN metastases had a prognostic impact were breast [27] and rectal cancer [28].…”
Section: Discussionsupporting
confidence: 87%
“…They then indicated that the regression change grading in LNs had an important role in survival analysis[8]. In the study of rectal carcinoma, there were 80% patients that had N0 disease[7], while there were 57.5% that had N0 disease in the study of esophageal carcinoma[8]. However, in our study, only 28% patients had no LN metastasis.…”
Section: Discussionmentioning
confidence: 59%
“…Newman et al[6] detected that after induction of chemotherapy for breast cancer, patients with negative axillary LNs but without regression change had the best outcome, those with positive axillary LNs but without regression change had the worst outcome, and those with pathological response of metastasis tumor in LNs had an intermediate outcome[6]. Fernández-Aceñero et al[7] found that ypN0 rectal carcinoma cases with regression change in LNs after neoadjuvant therapy showed a significantly worse prognosis when compared to the ypN0 cases without regression change in LNs. Bollschweiler et al[8] stratified esophageal carcinoma regression change in LNs after neoadjuvant therapy into three grades: low risk (no LN metastasis and fewer than 3 LNs with central fibrosis), medium risk (no LN metastasis and central fibrosis in 3 or more LNs, or LN metastasis with a LN ratio of less than 0.05) and high risk (all other cases).…”
Section: Discussionmentioning
confidence: 99%
“…In upper gastrointestinal cancers LN staging has a very high prognostic value [14]. For tumors treated with multimodal therapy, previous studies postulated that, not only the ypN status, but also the additional reporting and categorization of lymph node metastasis regression, may have important prognostic value [13,23,[29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%